PRODUCT PLACEMENT: FILM, PROGRAM TELEVISI, VIDEO GAMES, ATAU MUSIK ? - Zhendy Valentina Purnomo (Universitas Trunojoyo Madura, 2015)
Every companies manage to introduce their brand and product to community. Their effort to introduce their brand or products are to implement the marketing strategy. Effective marketing strategy can help the companies to achieve their goals. Promotion is one of the example of marketing strategy. Media campaign that mostly used nowadays is advertisement through television. There are many weakness in media television marketing. Therefore, marketing people already plan a new promoting strategy,that called product placement. Product placement can be very effective to companies to market their brand or even their products. Product placement media example is by placing advertisement in movies, television programs, video games, or music. Choosing appropriate product placement media can affect positively to the companies. Every product placement media has their own strength and weakness. This research aims to analyze which media is the most effective in product placement.